Increasing Community Literacy Through Regular Recitations in Rowotapen Tanggul Wetan Village Regarding Savings Products and Financing of BMT NU Tanggul Jember Branch - Musfiroh, Luluk; Nidiawati, Putri; Ratnasari, Itsnaini Aliyah (Jurnal Pengabdian Masyarakat, 2024)
Purpose: Community service activities in Rowotapen Tanggul Wetan Village aim to provide education to the community regarding savings and financing products of BMT (Baitul Mal wal Tamwil) NU Tanggul Branch which is aimed at providing understanding and awareness that there are sharia-based financial institutions.Method: The implementation of this service activity utilized a direct approach method with the community, namely through material presentation and discussions, to enable the community to have a deeper understanding of BMT NU Branch Tanggul.Practical Applications: This socialization activity is also expected to improve the well-being of the lower-income community without imposing pressure and to realize justice in accordance with Islamic law.Conclusion: The outcomes of this activity may include evaluations, feedback, and learning about Sharia-based financial institutions in the vicinity (KSPPS BMT NU Branch Tanggul).